The association between parental migration and early childhood nutrition of left-behind children in rural China - Huifeng Shi; Jingxu Zhang; Yufeng Du; Chunxia Zhao; Xiaona Huang; Xiaoli Wang (BMC, 2020)
Abstract Background More than one-third of children under 3 years old are left behind at home due to parental migration in rural China, and we know very little about early childhood nutrition of left-behind children (LBC) because of the dearth of research. This study examined the association between parental migration and early childhood nutrition of LBC in rural China. Methods We used repeated cross-sectional data of rural children aged 6-35 months who participated in two surveys in six counties of northern and southern China in 2013 and 2016 respectively. The length, weight, and hemoglobin concentration were measured by trained health-care workers blinded to parental migration status. Stunting, underweight, wasting, and anemia were identified with the standards recommended by WHO. Generalized linear regressions and multivariate logistic regressions were employed to explore the association between parental migration and these nutritional outcomes at each time point. Results Two thousand three hundred thirty-six and 2210 children aged 6-35 months were enrolled in 2013 and 2016, respectively. The results show a reduction of the risks of stunting, underweight, and wasting from 2013 (16.4, 8.5, and 3.5%, respectively) to 2016 (12.1, 4.0, and 1.5%, respectively) but highlight a constantly and alarmingly high risk of anemia among these children (44.8% in 2013 and 43.8% in 2016). Children with migrant fathers performed as well as or better than those with non-migrants on these indicators. Children with migrant parents performed slightly worse in 2013, but equal or slightly superior in 2016 on these indicators compared with children with non-migrants and migrant fathers. Children aged 6-17 months with migrant parents had a significantly lower risk of anemia than those living with their mothers or with both parents (43.1% vs. 63.6% and 61.5 in 2013, and 42.5 vs. 60.1 and 66.2% in 2016), even after controlling for children's sociodemographic characteristics. Conclusions Parental migration may be not detrimental and even beneficial to early childhood nutrition of LBC in rural China. Continued nutritional support is needed for all rural children, especially interventions for preventing micronutrient deficiency. Programs for LBC are recommended to continue to focus on nutrition but pay more attention to other important health issues.